Some reproduction aspects of Ephestia kuehniella Zeller (Lepidoptera, Pyralidae) under mass rearing conditions - Falp, Lluis (2011)
The Mediterranean flour moth, Ephestia kuehniella Zeller, is a serious cosmopolitan pest for cereal mills and wherever flour is stored, and in the Azores it is used to rear parasites and predators that are used in biological control (Trichogrammatidae, Coccinellídae, Chrysopidae). In order to leam the effect of mass rearing conditions on the reproduction of E. kuehniella, four groups of adult moths were studied: (i) isolated couples which were allowed to mate freely during all adult life, and which were not fed; (ii) isolated couples which mated freely and were fed with honey; (iii) couples that mated once and were not fed; (iv) virgins and were not fed. Differences between groups regarding weight, longevity, copulating behaviour, fecundity, fertility and number of spermatophores were evaluated. Females were heavier than males. Males and virgin females lived significantly longer than mated females. The oviposition was mainly concentrated in the first three days of the females lifetime (70-90% laying eggs). A high percentage (88%) of copulations occured within five hours before dawn. No significant differences were found in fecundiry and fertiliry parameters between females coupling once and those mating freely during lifetime, nor between those fed with or without honey. Virgin females laid lower numbers of eggs than mated females.